Implementasi Kebijakan Pemerintah Daerah Ponorogo tentang Ketertiban dan Kenyamanan di Kawasan Alon-Alon Kabupaten Ponorogo: Indonesia - Hilman, Yusuf Adam; Puthut Hermansyah; Wahjuni DJ, Ekapti; Nur Ridho, Irvan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2024)
This research aims to determine the implementation of regional policies in improving order and comfort for people carrying out trading activities and visitors, especially in the Alon-Alon Ponorogo area. This type of research is descriptive research aimed at describing what already exists and is applicable. Apart from that, descriptive research is also a problem-solving procedure that is investigated by moving and describing the current wealth of subjects, research objects (individuals, community institutions, etc.) based on visible facts. The results of this research are that the implementation of Ponorogo Regency Regional Government policies is carried out in a good manner, and full of togetherness, followed by high awareness among each interested party. In terms of controlling street vendors in Ponorogo, especially the Ponorogo Regency Square. There has been good communication between the government and the traders and no one has done anything to damage or harm the street vendors in that location. Keywords: Policy Implementation, Ponorogo Government